PENGARUH KOMPETENSI PEDAGOGIK, MOTIVASI KERJA DAN SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP KINERJAGURU SEKOLAH DASAR DI KECAMATAN WATES, KABUPATEN KULON PROGO TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research is intended to analyze: (1) The influence of paedagogic competence, working motivation, and headmaster academic supervision toward teachers‟ working motivation together, (2) The influence of paedagogic competence toward teachers‟ working motivation, (3) The influence of working motivation toward teachers‟ working motivation, and (4) The influence of headmaster academic supervision toward working motivation. This research was carried out in Wates District Kulon Progo Regency in the academic year of 2012/2013.The approach of this research was quantitative with survey methode. The population of this research was 240 of elementary school‟s teachers that was consisted of 6 group of elementry schools in Wates district Kulon progo regency. This research took 142 teachers with proportional random sampling technique. The data was collected by questionaires. The data analysis technique was using multiple regression with 3 predictors. The hypothesis test were done simultaneosly by with F- test then continued by using hypothesis test partially with t- test.The research result showed that paedagogic competence, working motivation, and headmaster academic supervision simultaneously gave positve influence and was very signifcant toward teachers‟ working motivation. The effective simultant contribution was 55,1%. Then the effective individual contribution were: (1) Paedagogic competence on teachers‟ working motivation was 6,85%, (2) Working motivation on teachers‟ working motivation was 33,11%, and (3) Headmaster academic supervision toward teachers‟ working motivation was 15,14%.